A stretchable elastomer with recyclability and shape memory assisted self-healing capabilities based on dynamic disulfide bonds. (1st March 2022) - Huang, Jiarong; Gong, Zhou; Chen, Yukun
Abstract: Shape memory assisted self-healing (SMASH) material is a kind of smart materials that can automatically close local microscopic cracks and heal those cracks by bonding the damaged surfaces. Here, we designed a SMASH elastomer via introducing polylactide (PLA) and disulfide bonds into the epoxidized natural rubber (ENR). PLA chains interspersed in ENR network as control switch to fix or release the temporary shape, providing ENR with enhanced mechanical strength and shape memory properties. After achieving the physical contact of crack surfaces by intrinsic shape memory, the exchange reaction of disulfide bonds healed the damaged area at elevated temperature. Meanwhile, the dynamic feature of disulfide bonds endowed ENR with recyclability, which could be further promoted by the thermoplasticity of PLA phase. Additionally, we also verified the feasibility of this strategy in designing PLA/ENR thermoplastic vulcanizate with SMASH behavior via dynamic vulcanization, expanding the research scope of self-healing elastomers and dynamic vulcanization. Graphical abstract: Image 1 Highlights: A simple method was proposed to design self-healing elastomer with recyclability. PLA was introduced to endow ENR with recyclability and shape memory capacity. The elastomer exhibited excellent shape memory assisted self-healing property. The proposed method was utilized to design self-healing thermoplastic vulcanizate.